Analisis Penerapan Strategi Digital Marketing dalam Upaya Meningkatkan Usaha Mikro Kecil Menengah di Kota Tangerang Selatan - Widodo, Arif Siaha; Armansyah, Armansyah; Wardani, Surti (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This research discusses the analysis of the implementation of digital marketing strategies in an effort to improve UMKM in the city of South Tangerang. The opportunities presented by increasing market demand and business digitalization can improve UMKM. The objectives of this research are 1) Identifying factors that need to be considered in a digital marketing strategy, 2) Making an Internal and External Analysis of the Company, 3) Formulating an appropriate digital marketing formulation, 4) Formulating a Company Operational Strategy. This research method is a combination of two methods, namely qualitative and quantitative with a survey method. The research instrument is a questionnaire with a Likert measurement scale of 1-9. The data collection technique uses company literature studies, interviews and questionnaires to find out the right marketing strategy, SWOT and AHP analysis are used. The result of this research is a score from the SWOT calculation on internal factors of 5.046 which is in the average category. Meanwhile, the internal score obtained from the analysis results was 5,206. The maximum score is a strategic location of 2.586. Weaknesses are shown in the minimum score of 0.296, namely the low level of technology adoption. The main strength that needs to be considered in implementing digital marketing strategies in improving UMKM in South Tangerang is the strategic location. The weakness that UMKM can overcome is the low level of technology adoption. Opportunities that can be exploited by UMKM are increasing market demand and digitalization of business. The threats that UMKM face are increasing production costs and online competition. However, with digital marketing through social media it does not become a significant obstacle in developing marketing.